A study on the effect of virtual communication skills education with a cognitive-behavioral approach on communication skills of midwifery personnel in healthcare centers - Sharifeh Golshahi; Soleiman Kheiri; Mohammad Rabiei; Behnaz Enjezab (Shahrekord University of Medical Sciences, 2022)
Background and aims: Effective communication between caregivers and clients is necessary for high-quality healthcare, and The ability to communicate with midwife caregivers is associated with better management of reproductive health problems in middle-aged women. This study aimed to investigate the effectiveness of communication skills training with a cognitive-behavioral approach to the communication skills of midwives in these people in the city of Shahrekord and the suburbs. Methods: This quasi-experimental single-group study was designed in a pretest-posttest approach, participating 51 midwife caregivers working on a questionnaire and Barton's standard communication skills questionnaire filled by the research units in the Porsline webpage before, immediately after the intervention, and one month later. The intervention included teaching communication skills with a cognitive-behavioral approach using virtual education packages weekly during six sessions through WhatsApp messenger. Where appropriate, data were analyzed using the parametric repeated measure ANOVA or Friedman test. Statistical significance was defined as P<0.05, and analysis was done by using SPSS 24. Results: The total communication skills were 65.2±5.6 in the pre-intervention phase and increased to 67.1±6.3 in the post-intervention stage. There was no significant difference in the subscales of verbal, listening, and feedback skills (P>0.05). Conclusion: Despite a positive effect on the midwives' communication skills, virtual education of communication skills with a cognitive-behavioral approach could not significantly change the field. Therefore, it is necessary to conduct further studies in the field to determine effective educational methods for retraining healthcare providers.